Adherence to the European Society of Cardiology/European Society of Anaesthesiology recommendations on preoperative cardiac testing and association with positive results and cardiac events: a cohort study. (September 2021) - Lurati Buse, Giovanna A.L.; Puelacher, Christian; Gualandro, Danielle Menosi; Kilinc, Derya; Glarner, Noemi; Hidvegi, Reka; Bolliger, Daniel; Arslani, Ketina; Lampart, Andreas; Steiner, Luzius A.; Kindler, Christoph; Wolff, Thomas; et al.
Abstract: Background: European Society of Cardiology/European Society of Anaesthesiology (ESC/ESA) guidelines inform cardiac workup before noncardiac surgery based on an algorithm. Our primary hypotheses were that there would be associations between (i) the groups stratified according to the algorithms and major adverse cardiac events (MACE), and (ii) over- and underuse of cardiac testing and MACE. Methods: This is a secondary analysis of a multicentre prospective cohort. Major adverse cardiac events were a composite of cardiac death, myocardial infarction, acute heart failure, and life-threatening arrhythmia at 30 days. For each cardiac test, pathological findings were defined a priori . We used multivariable logistic regression to measure associations. Results: We registered 359 MACE at 30 days amongst 6976 patients; classification in a higher-risk group using the ESC/ESA algorithm was associated with 30-day MACE; however, discrimination of the ESC/ESA algorithms for 30-day MACE was modest; area under the curve 0.64 (95% confidence interval: 0.61–0.67). After adjustment for sex, age, and ASA physical status, discrimination was 0.72 (0.70–0.75). Overuse or underuse of cardiac tests were not consistently associated with MACE. There was no independent association between test recommendation class and pathological findings ( P =0.14 for stress imaging; P =0.35 for transthoracic echocardiography; P =0.52 for coronary angiography). Conclusions: Discrimination for MACE using the ESC/ESA guidelines algorithms was limited. Overuse or underuse of cardiac tests was not consistently associated with cardiovascular events. The recommendation class of preoperative cardiac tests did not influence their yield. Clinical trial registration: NCT02573532 .